Venous Thromboembolism and Cerebrovascular Events in Patients with Giant Cell Arteritis: A Population-Based Retrospective Cohort Study - Lo Gullo, Alberto; Koster, Matthew J.; Crowson, Cynthia S.; Makol, Ashima; Ytterberg, Steven R.; Saitta, Antonino; Salvarani, Carlo; Matteson, Eric L.; Warrington, Kenneth J. (PloS one, 2016)
To investigate the incidence of venous thromboembolism (VTE) and cerebrovascular events in a community-based incidence cohort of patients with giant cell arteritis (GCA) compared to the general population. A population-based inception cohort of patients with incident GCA between January 1, 1950 and December 31, 2009 in Olmsted County, Minnesota and a cohort of non-GCA subjects from the same population were assembled and followed until December 31, 2013. Confirmed VTE and cerebrovascular events were identified through direct medical record review. The study population included 244 patients with GCA with a mean ± SD age at diagnosis of 76.2 ± 8.2 years (79% women) and an average length of follow-up of 10.2 ± 6.8 years. Compared to non-GCA subjects of similar age and sex, patients diagnosed with GCA had a higher incidence (%) of amaurosis fugax (cumulative incidence ± SE: 2.1 ± 0.9 versus 0, respectively; p = 0.014) but similar rates of stroke, transient ischemic attack (TIA), and VTE. Among patients with GCA, neither baseline characteristics nor laboratory parameters at diagnosis reliably predicted risk of VTE or cerebrovascular events. In this population-based study, the incidence of VTE, stroke and TIA was similar in patients with GCA compared to non-GCA subjects.